Deaths among the elderly with ICU infections - Álvaro Francisco Lopes de Sousa; Artur Acelino Francisco Luz Nunes Queiroz; Layze Braz de Oliveira; Luana Kelle Batista Moura; Denise de Andrade; Evandro Watanabe; Maria Eliete Batista Moura
ABSTRACT Objective: to evaluate the clinical outcome of elderly patients admitted to intensive care units who had nosocomial infection, correlating the findings with sociodemographic and clinical variables. Method: descriptive research, performed with 308 elderly patients. The collection was made from medical records and covers the years 2012 to 2015. Uni-/bivariate analyses were performed. Results: a statistical association was found between the clinical outcome types and the variables age, length of stay, presence of previous comorbidities, main diagnosis, respiratory and urinary tract infections, use of central venous and indwelling urinary catheters, mechanical ventilation, and tracheostomy. The survival curve showed higher mortality among the elderly from the age of 80 on. Conclusion: the clinical outcome of the elderly who acquire infection in the intensive care unit is influenced by sociodemographic and clinical variables that increase mortality rates.